Corneal dystrophy in a cocker spaniel dog: a case report - Monica Ragusa; Michela Pugliese; Domenico Britti; Ernesto Palma; Antonio Pugliese (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2017)
A 1-year-old female Cocker Spaniel dog was examined at the ophthalmology service of the Veterinary Teaching Hospital - University of Messina (Italy) for evaluation of symmetrical white spots in both corneas and “red eyes”. Dog was clinically healthy, haematological and biochemical examination were unremarkable, Leishmania PCR was negative. After a complete ophthalmic examination, the clinical diagnosis was corneal stromal dystrophy with uveitis-induced. In dogs, corneal stromal dystrophy is a primary, inherited, bilateral opacity of the corneanot associated with ocular inflammation or systemic disease. Detailed description of corneal dystrophy are available only for few breeds. This lesion is not progressive and treatment is not usually recommended unless vision is impaired or the deposits become irritating.